Comparative analysis of receptive vs. productive vocabulary knowledge among adult language learners - Murtozoyeva, Shodiya (The Lingua Spectrum, 2025)
This article presents a comparative analysis of receptive and productive vocabulary knowledge among adult language learners. It explores the distinctions between these two types of vocabulary, emphasizing their implications for language acquisition and teaching. The study is grounded in theoretical models proposed by Nation, 2001 & Schmitt, 2000, highlighting the cognitive differences between understanding vocabulary and using it in communicative contexts. A mixed-methods approach was employed, incorporating both quantitative assessments—using the Vocabulary Size Test (VST) and the Productive Vocabulary Levels Test (PVLT)—and qualitative insights through interviews and questionnaires. Findings reveal that while learners demonstrate stronger receptive vocabulary skills, their productive vocabulary remains limited, with average scores of 75% and 55% respectively. This gap is attributed to factors such as insufficient output-based practice, language anxiety, and limited contextual exposure. The article discusses pedagogical recommendations, including interactive speaking tasks, guided writing exercises, and enhanced lexical activation strategies, aimed at narrowing this disparity and fostering balanced vocabulary development in adult learners.